KESALAHAN SINTAKSIS PADA STRUKTUR KALIMAT TEKS ANEKDOT SMA NUR CAHAYA - Putri Sion Dameria Br Silaen; Dairi Sapta Rindu Simanjuntak; Indah Lestari Sinulingga; Sura Bina Barus; Angelica Renata Sipayung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of syntactic errors in sentence structures found in anecdotal texts written by tenth-grade students of SMA Nurcahaya. The research employed a descriptive qualitative method. The data consisted of students’ written anecdotal texts collected through a writing test. The research subjects were 12 students of class X at SMA Nurcahaya. Data collection techniques included reading and note-taking, while data analysis was conducted by identifying, classifying, and describing syntactic errors found in the students’ writings.The results of the study indicate that various syntactic errors were found in the sentence structures of the students’ anecdotal texts. These errors include mistakes in subjects, predicates, direct objects, indirect objects, benefactive objects, subject attributes, object attributes, and predicate complements. The most frequent errors were the use of non-standard words, incorrect placement of sentence elements, omission of obligatory sentence components, and improper use of affixes according to Indonesian grammatical rules. These errors were influenced by students’ limited understanding of standard sentence structures, the influence of spoken language, and the use of foreign terms.